Method for producing optical components with improved surface quality using additive manufacturing

By applying and hardening the hardenable coating liquid layer on the additively manufactured ophthalmic lens optical element, the step pattern problem caused by additive manufacturing is solved, and the smooth surface and efficient optical function of the optical element are achieved.

CN114867597BActive Publication Date: 2025-04-25ESSILOR INTERNATIONAL(COMPAGNIE GENERALE D OPTIQUE)
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202080088726.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-12-23
Filing Date
2020-12-23
Publication Date
2025-04-25
Estimated Expiration
2040-12-23

AI Technical Summary

Technical Problem

When the existing additive manufacturing methods are made in ophthalmic lenses, discrete patterns or step patterns appear on the surface of the optical element, resulting in poor optical functions, and the film or diaphragm used may cause deformation of the optical element or uneven spread of the resin.

Method used

By successively gathering predetermined volumes of elements of polymerizable material, the optical element is fabricated using an additive manufacturing process and applying and spreading a hardenable coating liquid layer on the unfinished surface to harden to fill the recesses to form a smooth peripheral surface.

Benefits of technology

The smooth outer surface of the optical element is realized, the accuracy and acceptability of optical functions are improved, and the deformation of the optical element and the uneven spread of the resin are avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114867597B_ABST
    Figure CN114867597B_ABST
Patent Text Reader

Abstract

A method for manufacturing an optical component having at least one optical function, comprising: manufacturing at least a portion of an optical element (40) using an additive manufacturing process by depositing a plurality of predetermined volume elements (14) of a polymerizable material, the portion of the optical element (40) being configured to provide at least a portion of the optical function of the optical component, the additive manufacturing being performed such that the optical element (40) comprises an unfinished peripheral surface (42), the unfinished peripheral surface (42) having a relief pattern (44) formed by traces of the additive manufacturing process and having at least one depression (18) relative to another portion of the peripheral surface (42); coating the unfinished peripheral surface (42) with a layer (50) of a coating liquid (46), the coating liquid being configured to at least partially fill the at least one depression (18).
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention relates to the manufacture of optical components, such as ophthalmic lenses.

[0002] More specifically, the present invention relates to a method of manufacturing an ophthalmic component by additive manufacturing.

[0003] Methods for manufacturing ophthalmic components by additive manufacturing are well known. The optical element is formed by depositing a plurality of predetermined volumes of material, which may be a material layer or a plurality of voxels, i.e., elementary volumes of material, which are formed within the same layer, or by depositing droplets, each droplet being a voxel.

[0004] The deposition of the predetermined volume of material induces a discrete pattern or a staircase pattern in three dimensions, in particular in the inclined or curved areas of the optical element. When the optical element is an ophthalmic lens or a part thereof, such a pattern does not allow obtaining the desired optical function, since the roughness is too high, making this surface unacceptable for optical applications.

[0005] A solution to this staircase pattern is disclosed, for example, in WO 2017 / 062857 A1, in which a film or a diaphragm is used to spread the resin onto an optical element obtained by additive manufacturing in order to smooth the peripheral surface of the optical component. However, if the film is too hard or if the optical element has not yet been fully cured, the film or diaphragm may deform the optical element or spread the resin unevenly. Conversely, if the film is too easily stretched, it may not allow the step pattern to be reduced to a completely satisfactory level, thereby retaining the imprint of the step pattern.

[0006] The problem that the present invention aims to solve is therefore to provide an improved method which allows the manufacture of an ophthalmic component with a smooth peripheral surface providing a precise optical function.

[0007] In order to solve this problem, the present invention provides a method for manufacturing an optical component having at least one optical function, the method comprising:

[0008] - manufacturing at least a portion of an optical element configured to provide at least a portion of an optical function of an optical component using an additive manufacturing process by successively aggregating a plurality of predetermined volume elements of a polymerizable material, said additive manufacturing being performed such that the optical element comprises an unfinished surface having a relief pattern formed by traces of the additive manufacturing process and having at least one depression relative to an average curved surface of the surface,

[0009] - applying and spreading a layer of a hardenable coating liquid to the unfinished surface, the hardenable coating liquid being configured to at least partially fill the at least one recess,

[0010] - Hardening the hardenable coating liquid layer.

[0011] The present invention further provides a method for manufacturing an optical element, the method comprising providing an optical element with a surface, the surface having a step pattern such that the optical element is not completely smooth, the method comprising:

[0012] - applying and spreading the hardenable coating liquid on the surface of the optical element so as to cover the step pattern of the optical element,

[0013] - hardening the hardenable coating liquid present on the surface;

[0014] Here, before applying the hardenable coating liquid, the surface having the step pattern is an unfinished surface.

[0015] The inventors have noticed that providing the surface in an unfinished state prior to coating improves the process along two axes. Firstly, the spreading of the hardenable material on the unfinished surface is improved compared to the spreading on a finished or hardened surface due to improved wetting properties. Furthermore, this unfinished state allows promoting the adhesion of the coating liquid to the surface when the coating hardens.

[0016] This improved wettability allows the use of a coating liquid that can fill the depressions formed by the concave-convex pattern without forming air inclusions; in addition, the improved wettability enables the use of a coating liquid with self-leveling properties that can smooth the depressions of the concave-convex pattern. Both aspects can provide a continuous outer surface. The outer surface of the optical element is thus smooth, allowing the optical element to improve its ability to meet the desired optical function.

[0017] Furthermore, the coating liquid hardens together with the unfinished portion of the unfinished surface, thereby improving adhesion.

[0018] According to an embodiment of the manufacturing method, the unfinished surface is at least partially uncured before the coating step. Therefore, when hardened, the hardenable coating liquid may partially merge with the material from the unfinished surface, thereby reducing the occurrence of an interface between the two layers. Therefore, it improves the ability of the optical element to provide a desired optical function.

[0019] Thus, before the coating step, the unfinished surface is partially but not completely cured. This partial curing allows the surface to promote adhesion of the coating liquid.

[0020] According to an embodiment of the manufacturing method, the unfinished surface is formed by an external volume element that forms an optical element, and the external volume element has a non-zero polymerization rate that is less than or equal to light that has received 2 times with a cured surface energy representing Jacobs energy.

[0021] According to an embodiment of the manufacturing method, the unfinished surface is an inhibited layer formed by end portions of volume elements forming the surface portion of the optical element and in which polymerization has been inhibited during the additive manufacturing process.

[0022] When the optical element is additively manufactured, an inhibited layer is formed on the outer surface of the optical element. The inhibited layer is characterized by a gradient of reduced conversion rate from the optical element below the inhibited layer to the air. The formation of the layer results from the inhibition of polymerization by at least one inhibitor substance, which is capable of quenching the initiation of polymerization or terminating polymerization. In the case of free radical chain growth polymerization, molecular oxygen can act as an inhibitor during additive manufacturing. Active free radicals generated under radiation are quenched by oxygen at the surface of the printed layer.

[0023] This suppressed state of the outer layer (which is typically undesirable according to standard processes, avoided or removed by cleaning, or fully cured in a final curing step) is used as a benefit according to this embodiment of the present disclosure to promote wetting and adhesion, and therefore enable smoothing of step patterns produced by additive manufacturing.

[0024] According to an embodiment of the manufacturing method, the coating step comprises solidifying the coating liquid layer deposited on said unfinished surface.

[0025] This curing step allows the coating liquid layer to be fully cured to complete the optical element, or only partially cured to promote adhesion of another cured liquid layer. This curing can be configured to also fully cure or complete the unfinished surface below the coating liquid.

[0026] According to an embodiment of the manufacturing method, the predetermined depression of the surface is obtained by curing under an oxygen-containing atmosphere, in particular during the additive manufacturing of the unfinished surface.

[0027] According to an embodiment of the manufacturing method, the last layer of coating liquid present on the optical component is cured in an oxygen-free atmosphere.

[0028] According to an embodiment of the manufacturing method, the hardenable coating liquid is a polymerizable coating liquid.

[0029] According to an embodiment of the manufacturing method, the hardenable coating liquid comprises at least one type of initiator suitable for initiating polymerization of the polymerizable material used for manufacturing the optical element.

[0030] According to an embodiment of the manufacturing method, the polymerizable material forming the outer predetermined volume element of the optical element and the hardenable coating liquid comprise the same monomer.

[0031] This facilitates the merging between the unfinished peripheral layer and the coating liquid. Furthermore, providing the unfinished peripheral layer and the coating liquid with the same material allows to have the same refractive index, thereby avoiding to limit undesired optical effects.

[0032] In a particular embodiment, the hardenable coating material comprises, in addition to the polymerizable material forming the outer predetermined volume element of the optical component, additives adapted to improve the rheological properties of the hardenable coating material, such as spreading properties or leveling properties.

[0033] According to an embodiment of the manufacturing method, the absolute difference between the refractive indices of the polymerizable material forming the outer predetermined volume element of the optical element in the hardened state and the hardenable coating liquid in the hardened state is smaller than 0.02, preferably smaller than or equal to 0.01.

[0034] According to an embodiment of the manufacturing method, the manufacturing method further includes applying and spreading at least one additional hardenable coating liquid layer onto the hardenable coating liquid layer or onto another additional hardenable coating liquid layer, and making the hardenable coating liquid layer or the other additional hardenable coating liquid layer only partially cured before applying and spreading the additional hardenable coating liquid layer.

[0035] In doing so, the method provides multiple coatings for reducing step patterns. Thus, the outer surface of the optical element is even smoother or has better precision than smoothing using a single layer of coating material, while the total thickness of the hardenable coating material applied is similar. In turn, it allows the use of a smaller total thickness of the hardenable coating material to obtain a similar level of smoothness as obtained using a single thicker coating level. It also allows the process to be more flexible by selecting the degree of smoothing or other parameters of the outer surface.

[0036] According to a variant of said embodiment, before applying and spreading the additional coating liquid layer, the coating liquid layer or the further additional coating liquid layer is at least partially uncured or has inhibited end portions in order to promote adhesion of the additional coating liquid layer thereto.

[0037] According to an embodiment of the manufacturing method, a different coating liquid can be used on the previous coating. The coating liquid used has an adjusted rheological or mechanical behavior (higher or lower viscosity, higher or lower self-leveling ability).

[0038] According to an embodiment of the manufacturing method, the coating and potential additional coatings provide the optical element with a smoothing layer having a total thickness greater than the depth dimension of the recess and / or greater than the average thickness dimension of the predetermined volume elements, preferably greater than or equal to at least 1.5 times this depth dimension.

[0039] This definition of the thickness of the smoothing layer allows ensuring that the recesses are filled with the coating liquid and that the outer surface of the optical element is smoothed. Furthermore, monitoring the thickness of the smoothing layer allows making the layer have a thickness sufficient to smooth the outer surface but not too high, thereby optimizing the amount of material used and ensuring that the desired geometry of the optical element is maintained. In practice, in the case of an optical element intended to be an ophthalmic lens designed to be suitable for use in spectacles, the optical surface can be a complex surface, potentially having two or more areas with different optical powers. Accordingly, there is a conflict between ensuring that the complexity of the optical surface of the lens is maintained and smoothing local recesses and steps.

[0040] According to an embodiment of the manufacturing method, said predetermined inhibition of the end portion is obtained by curing the successive hardenable coatings under an atmosphere comprising an inhibitor, such as molecular oxygen.

[0041] According to an embodiment of the manufacturing method, the manufacturing method comprises fully curing a final hardenable coating liquid layer present on the optical component.

[0042] This final curing step allows the optical element to obtain a tack-free or non-sticky surface.

[0043] According to an embodiment of the manufacturing method, the unfinished surface of the optical element is not completely cleaned before the applying step and the spreading step, so that before applying and spreading the hardenable coating liquid layer on said unfinished surface, the surface comprises a layer or sublayer of curable liquid material.

[0044] According to an embodiment of the manufacturing method, the applying step and the spreading step are performed by at least one of a dipping process, a spraying process, a spin coating process, an inkjet process, and polymer jetting.

[0045] All of these processes allow for the distribution of the hardenable coating liquid across the unfinished surface to help smooth the outer surface of the optical element.

[0046] According to an embodiment of the manufacturing method, the optical element comprises a plurality of layers formed by the plurality of volume elements and forming a curved profile curve, and the concavo-convex pattern of the surface is a step pattern formed by edges of the layers.

[0047] The invention is described in more detail below by means of the accompanying drawings which show several preferred embodiments of the invention.

[0048] Figure 1 An optical element obtained by depositing a predetermined volume by additive manufacturing is schematically shown.

[0049] Figure 2 An optical element is schematically shown with an unfinished surface on top of the optical element.

[0050] Figure 3An optical element is schematically shown, with a hardenable coating liquid applied to its unfinished surface.

[0051] Figure 4 A plurality of coatings applied to an unfinished surface of an optical element is schematically shown.

[0052] Figure 5 A fully cured optical element with a smooth outer surface is schematically shown.

[0053] Figure 6 The conversion rate of the curable material is shown as a function of the energy supplied thereto.

[0054] Figure 7 The expected thickness of a layer is shown as a function of the natural logarithm of the energy supplied to it.

[0055] Figure 8 A detailed view of the surface of an optical element is schematically shown.

[0056] Fig. 9 A flow chart of an embodiment of a manufacturing method for controlling acceptance requirements is shown.

[0057] like Figure 1 As shown, an optical element 40 is obtained by additive manufacturing, i.e. by depositing a plurality of predetermined volume elements 14, which are juxtaposed and superimposed to form a plurality of superimposed material layers. The optical element 40 is part of an optical component, which may be an ophthalmic lens. The optical element 40 is formed, for example, on a build support 30. Alternatively, the optical element 40 may be manufactured without any build support 30.

[0058] The optical element 40 is manufactured relative to a three-dimensional axis system, which includes a first surface axis X and a second surface axis Y, which define a plane on which the layer of volume elements 14 extends. The three-dimensional axis system also includes a height axis Z relative to the thickness of the layer of volume elements 14.

[0059] The predetermined volume element 14 may be a material layer or a plurality of voxels, i.e., a basic volume of material defined by an additive manufacturing technique: a material droplet for inkjet printing, an exposure resolution in stereolithography, a plurality of voxels irradiated together with the same material layer, different layers of such a group of voxels formed on top of each other, a raw material size in fused deposition. Thus, the optical element 40 may include at least one of a plurality of layers and a plurality of voxels.

[0060] It should be noted that additive manufacturing here corresponds to three-dimensional printing or stereolithography methods, or even fused filament manufacturing methods. Preferably, additive manufacturing is one of stereolithography (SLA), digital light processing stereolithography (DLP-SLA) or (photo) polymer jetting. An advantage of polymer jetting technology is that an additive manufacturing machine can have multiple print heads using different materials. Additive manufacturing technology includes a variety of methods that create an object by juxtaposing multiple volume elements according to a predetermined arrangement that can be defined in a CAD (computer-aided design) file.

[0061] Both stereolithography (SLA) and digital light processing stereolithography (DLP-SLA) work by focusing light (primarily UV light) onto a container of photocurable liquid resin to form solid layers that are stacked up to form a solid object. With stereolithography (SLA), the liquid resin receives selective exposure by scanning the print area with a laser beam. Digital light processing stereolithography (DLP-SLA) uses a digital projector screen to project the image of each layer onto the entire surface of the resin. Since the projector is a digital screen, the image of each layer consists of clearly square pixels, resulting in layers formed by small rectangular blocks called voxels (the volume is defined by the square pixels and the thickness of the layer).

[0062] Alternatively, the pixels may have other shapes, such as hexagonal, diamond or elongated, depending on the technology used to form the image, for example LCD or LED or DMD (micromirror) pixels.

[0063] Polymer jetting technology uses an inkjet printhead to eject droplets of curable liquid resin onto a build platform. The liquid resin is immediately cured by a curing unit (such as a heat source or light source) and solidifies droplet by droplet to build a layer or final optical element (and form a solid object).

[0064] In practice, the additive manufacturing technology used here is based on the projection of a light pattern on a curable material. The light of the pattern comes, for example, from an infrared light source or a microwave source or a UV light source. The curable material is, for example, a photopolymer / photocurable resin based on a (meth)acrylate monomer / oligomer containing a sulfur atom in the main chain, and the optical element is manufactured when all the volume elements are deposited and the polymerization of the monomers is fully completed.

[0065] In practice, the photopolymerization process can be characterized by the monomer conversion Cv (or inappropriately "polymerization rate") of the curable material. The conversion Cv is related to the physical state of the substance of the curable material. Before being irradiated by curable energy, mainly light, the curable material is in a liquid state. The conversion Cv is considered to be close to 0, although there is a slight polymerization due to the aging of the curable material. Under the irradiation of the curable surface energy on the curable material, the curable material polymerizes and gradually changes from a liquid state to a solid state. The curable material will go through a variety of states, especially an intermediate state (called a "gel state"), and its corresponding conversion Cv depends on the composition of the curable material. The intermediate state corresponds to a state of matter that is neither liquid nor solid but between them, especially not strong enough to be manipulated without damaging or deforming the parts, but the monomers have begun to polymerize with each other and begin to form part of the polymer network. The conversion Cv of the intermediate state of some acrylate monomers can be, for example, between 10% and 80%, or the conversion of the intermediate state of some other monomers is higher than 5% and / or lower than 67%. For a conversion Cv that is generally above 70%, the curable material is considered to be in the solid state. For some acrylate monomers, for a conversion Cv that is above 40%, the curable material is considered to be in the solid state. Depending on the material, the curable material is considered to be in the solid state for a conversion above a critical conversion, which can be empirically determined to be between about 40% and about 100%.

[0066] A portion of the optical element 40 is configured to provide at least a portion of the optical function of the optical component.

[0067] It will be recalled that the optical function of a lens, system or optical element refers to the optical response of the lens or the system or the element, i.e. the function defining any variation of the propagation and transmission of a light beam through the lens, system or optical element concerned, whatever the angle of incidence of the incident light beam and whatever the geometric range of input diopters illuminated by the incident light beam. The at least one optical function may be simple or complex.

[0068] More precisely, in the field of ophthalmology, optical function is defined as the distribution of the wearer's power and astigmatism characteristics and the distribution of higher-order aberrations associated with the lens, system or optical element for all gaze directions of the wearer of the lens, system or optical element. This of course assumes that the geometric positioning of the lens, system or optical element relative to the wearer's eye has been predetermined.

[0069] It will also be noted that the wearer power is a way of calculating and adjusting the power of an ophthalmic lens, which is different from the focometric power. Calculating the wearer power ensures that once the lens is positioned in the eyeglass frame and worn by the wearer, the power perceived by the wearer (i.e., the power of the light beam entering the eye) corresponds to the prescribed power. In general, for progressive lenses, the power measured using a lensometer is different from the wearer power at any point on the lens, especially at the points where distance and near vision are checked. However, the wearer power at the optical center of a single-vision lens is usually close to the power observed using a lensometer located at this point.

[0070] Depending on the desired optical function of the optical component, the front and back sides of the optical element 40 can each be planar or curved. The shape or predetermined profile of the optical element 40 is determined depending on the desired optical function of the optical component. A "curved" surface means that the surface defines a profile with a non-zero curvature.

[0071] exist Figure 1 and Figure 2 In the embodiment of the present invention, the optical element 40 is partially manufactured. In other words, the manufacture of the optical element 40 is not completed, so that the optical element 40 does not obtain its final shape or profile curve.

[0072] The optical element 40 includes a surface 42. The surface 42 forms a concave-convex pattern 44 on the optical element 40. The concave-convex pattern 44 is formed by the traces of the additive manufacturing process. The concave-convex pattern 44 is in the form of a step pattern, wherein each step is formed by the edge of the volume element 14. The concave-convex pattern 44 forms a recess 18 relative to another part of the surface 42. In particular, the recess 18 is formed between two end portions or two edges of consecutive volume elements 14.

[0073] like Figure 2 As shown, the surface 42 is a layer of material formed by the end portion or surface of the optical element 40. Therefore, the surface 42 has a non-zero thickness. The surface 42 forms 5% to 100% of the thickness of the additively manufactured layer. In other words, the surface 42 extends from the upper surface of the layer made of the volume element 14 and has a thickness between 5% and 100% of the thickness of this layer. The additively manufactured layer typically has a thickness of 1 μm to 200 μm.

[0074] The additive manufacturing process is performed such that the surface 42 is unfinished.

[0075] By "unfinished" it is meant that the layer with the unfinished surface 42 has, over at least part of its thickness and at least over the unfinished surface, a conversion or polymerization rate that is lower than that desired for the finished optical element: for example, before the applying step and the spreading step, the layer is at least partially uncured and has a non-zero conversion or polymerization rate over at least part of its thickness. This portion of the thickness of the layer may be referred to as a sublayer, since it is typically thinner than a typical layer used in a corresponding additive manufacturing process or other layers of hardenable material applied according to the present disclosure. In other words, the unfinished layer or layer with an unfinished surface is at least partially polymerized, but not completely polymerized. The unfinished layer or layer with an unfinished surface is a non-completely solid layer in the sense of Jacobs. As an extreme illustration, the layer with the unfinished surface may be completely a non-solid gel material, or, conversely, as the exact opposite case, solid in the sense of Jacobs for most of its thickness, the uncleaned surface providing the surface with only a thin coating of completely uncured curable liquid material (between 5% and 50% of the layer thickness). Most applications of the present invention may lie between these two cases.

[0076] By "uncured" or "partially uncured" it is meant that the surface 42 has at least an outer layer or sublayer of curable material in a liquid state or in an intermediate state between a liquid and a solid state, while having a non-zero conversion rate.

[0077] "Partially uncured" therefore includes having an outer liquid layer or sublayer on the surface, an outer layer or sublayer in an intermediate state, or an outer layer or sublayer that is solid enough to be manipulated and has a conversion or polymerization rate that can be significantly increased by a subsequent curing step, for example: the material still contains unpolymerized monomers.

[0078] In embodiments where the surface 42 is partially uncured, the surface 42 of the optical element 40 is not fully cleaned prior to depositing the hardenable coating liquid 46. The purpose of not fully cleaning is to preserve / protect the partially uncured layer or the inhibited layer.

[0079] "Not completely cleaned" means that during the application and spreading of the hardenable coating liquid layer, the device manufactured before the application of the hardenable coating liquid layer already includes a thin layer or sublayer of the curable liquid material already present on its surface. In other words, the surface of the optical element 40 is covered with the thin layer of liquid curable material just before the hardenable coating liquid 46 is applied or spread.

[0080] In one embodiment, incomplete curing maintains a layer of liquid of polymerizable material used to additively manufacture these predetermined volume elements forming the optical element atop said outer polymerized or partially polymerized predetermined volume elements of the optical element. It can improve adhesion and merge the hardenable coating liquid with the inhibited layer. Incomplete cleaning can include rinsing with a shorter solvent exposure duration, or using only drainage, but this still leaves a thin layer of liquid on the manufactured device.

[0081] Then, the unfinished surface 42 is coated with a layer of a hardenable coating liquid 46, which is configured to at least partially fill at least one recess 18. It has been observed that maintaining the surface 42 as unfinished promotes the wetting of the hardenable coating liquid 46 on the surface 42. The improved wettability provided by the unfinished surface 42 allows the hardenable coating liquid to stretch itself and flatten itself to fill the recess 18 formed by the concave-convex pattern 44. In addition, maintaining the surface 42 as unfinished promotes the adhesion of the hardenable coating liquid 46 to the surface 42. The hardenable coating liquid 46 merges with the material of the unfinished surface 42, thereby reducing the appearance of an interface between the two layers. This significantly improves the ability of the optical element 40 to provide the desired optical function.

[0082] The hardenable coating liquid 46 deposited onto the unfinished surface 42 is then cured to harden the layer of hardenable coating liquid 46. Depending on the amount of hardenable coating liquid 46 to be deposited, the hardenable coating liquid 46 is partially cured or completely cured. Figure 4 As shown, multiple layers of hardenable coating liquid 46 may be deposited.

[0083] When depositing multiple layers of hardenable coating liquid 46, the previously deposited hardenable coating liquid 46 corresponds to the first layer 50 of hardenable coating liquid 46. In this case, the first layer 50 is only partially cured to promote adhesion of another layer of hardenable coating liquid 46. In other words, the first layer 50 is maintained unfinished. An additional layer 52 of hardenable coating liquid 46 is deposited onto the first layer 50 of hardenable coating liquid 46. Multiple additional layers 52 of hardenable coating liquid 46 can be deposited to obtain the final shape of the optical element 40. Each additional layer 52 is only partially cured, i.e., maintained in an unfinished state, to promote adhesion and wetting of another layer of hardenable coating liquid 46. Figure 5 As shown, the optical element 40 is then fully cured so that the entire optical element 40 is hardened into a solid state.

[0084] like Figure 5 As shown, when a single layer of hardenable coating liquid 46 is deposited onto the unfinished surface 42, the hardenable coating liquid 46 is then fully cured to harden the entire optical element 40 into a solid state.

[0085] Thus, a continuous and smooth outer surface 48 can be obtained, thereby improving the ability of the optical element 40 to meet the desired optical function. A "continuous and smooth" surface refers to a surface without any concave-convex pattern or with a reduced concave-convex pattern; for example, a surface with a concave-convex pattern of at least less than 1 μm or even less than 500 nm. In particular, the concave-convex pattern is such that H <KT 2 , where H is the amplitude of the height variation from the target surface, T is the period of the wave formed by the relief pattern, and K is a constant that depends on the refractive index and manufacturing tolerances. In particular, this means that H and T must obey the following equation:

[0086]

[0087] Where H = the height change from the target surface (in μm)

[0088] ΔP = industry tolerance, which is less than 0.12 diopters, or 0.06 diopters, or even 0.02 diopters, depending on the target quality of the optical lens.

[0089] T = period or "wavelength" of the relief pattern (in millimeters).

[0090] n = refractive index of the material

[0091] As an example, for a hardened coating material with a refractive index of 1.5 (which is one of the lowest for eyeglass lenses) and the highest industry tolerances, the maximum height of the relief pattern, depending on its wavelength, for the surface to be considered continuous and smooth can be found in Table 1.

[0092] T(mm) H(μm) 1 0.012 2 0.049 3 0.109 4 0.195 5 0.304 6 0.438 7 0.596 8 0.778 9 0.985 10 1.216

[0093] Table 1

[0094] It should be noted that usually the term "roughness" is determined for a concave-convex pattern with a wavelength of less than 1 mm. The optical surface of the eyeglass is considered to be smooth if the Ra (arithmetic mean of the amplitude) is less than or equal to 10 nm.

[0095] This multilayering of the hardenable coating liquid 46 can be configured to produce a gradient of thermomechanical properties or optical properties. As an example, the material can be selected so that scratch resistance is improved, or polishing after coating is made easier. This can be achieved by changing the curable material itself of one or more layers of the hardenable coating liquid, or an increased percentage of a hardener or colloid can be added to the curable material. In addition, in order to make the optical element 40 have better impact resistance, the softening of the material can be selected. These multiple layers can form a bandpass filter for cutting off a predetermined wavelength (for harmful blue light).

[0096] Using either the first or second embodiment, the surface 42 can remain unfinished. The same embodiment can be used to make an unfinished hardenable coating liquid 46 layer.

[0097] According to a first embodiment, the unfinished surface 42 is an inhibited layer or sub-layer of the outer layer of hardened material. In other words, polymerization of the surface 42 has been inhibited during the additive manufacturing process to maintain the surface as unfinished.

[0098] After an object is printed using additive manufacturing, an inhibited layer is formed at the periphery of the object, and the inhibited layer is characterized by a gradient of reduced conversion rate from the part to the air. The inhibited layer or sublayer is formed by the inhibition of polymerization by molecular oxygen during printing. Therefore, the layer is printed or cured under molecular oxygen or normal atmosphere to maintain the polymerization inhibition phenomenon. The active free radicals generated under radiation are quenched by molecular oxygen at the surface of the printed layer. In the field of coating, great efforts have been made to avoid the formation of such an inhibited layer during / after curing. In this first embodiment, the surface 42 is intentionally formed as an inhibited layer or sublayer to promote the adhesion and spreading of another material layer and reduce the appearance of interfaces between layers.

[0099] As the surface 42 is applied and spread, the inhibited layer is replenished with initiators by diffusion. These initiators are protected from the effects of molecular oxygen. As the hardenable coating liquid 46 polymerizes or cures, the previous inhibited layer or sublayer (the surface 42 or hardenable coating liquid 46 layer) also polymerizes and a new inhibited layer is formed on top of the hardenable coating liquid 46. This configuration of depositing a new coating onto an inhibited layer or sublayer and then partially curing allows the new coating to merge with the previous inhibited layer, thereby merging with the already fabricated volume element 14.

[0100] In this first embodiment, the last layer of hardenable coating liquid 46 of optical element 40 is deposited in an oxygen-free atmosphere to complete the last layer. Once the last layer is applied, the steps are smoothed and the optical element 40 is placed in an oven in an inert atmosphere (e.g., nitrogen) to avoid oxygen inhibition and to definitively cure the optical element 40. This last layer of hardenable coating liquid 46 is the first layer 50 when depositing a single layer on optical element 40, and the last layer is an additional layer 52 when depositing multiple coatings.

[0101] According to the second embodiment, the surface 42 is made unfinished by adjusting the total curing energy (or light dose) provided during the additive manufacturing process to the predetermined volume elements forming the surface 42. The "last curing energy" refers to the last irradiation provided by the light source before the layer of hardenable coating liquid 46 is deposited.

[0102] Accordingly, during the additive manufacturing process, the curing energy received by the curable material of the surface 42 is limited to be insufficient to completely harden the curable material, thereby maintaining it uncured. Therefore, the surface 42 is only provided with a predetermined light dose that allows the curing process to begin, but does not reach a light dose value that can completely cure the surface 42.

[0103] Adjusting the light dose provided to the curable material allows the polymerization rate (or conversion rate) of the curable material to be controlled. In fact, the conversion rate characterizing the intermediate state and the solid state depends on the curing surface energy E (or light dose) from the light source, the absorption characteristics of the curable material, and the efficiency of the initiator to polymerize the curable material.

[0104] Figure 6 A graph showing the conversion rate Cv (in %) as a function of the curing surface energy E of the irradiated curable material is shown.

[0105] In the current embodiment, the light dose provided to the surface 42 is adjusted to be lower than or equal to the Jacob energy amount Ej. This makes the volume elements forming the surface partially uncured, that is, at least a portion of each volume element forming the surface is uncured. In a variant, in the current embodiment, the light dose provided to the surface 42 is adjusted to be lower than or equal to the critical Jacobs energy Ec, for example greater than 0.3*Ec. This makes the volume elements forming the surface uncured: that is, in an intermediate state, while polymerization has still been initiated. For example, if the volume element is a voxel, such as a voxel formed by inkjet deposition of a drop of material, or a voxel formed by irradiating pixels on a layer of liquid material, the voxel forming the surface is in an intermediate state.

[0106] It should be noted that if the curable material forming the surface 42 receives a light dose that is higher than the Jacobs energy but lower than 3 times the Jacobs energy (which corresponds to a curing surface energy represented by the Jacobs energy (Ej)), while still lower than the energy required to achieve complete conversion, then a predetermined volume element of the surface may be in an unfinished state within the meaning of the present disclosure, rather than being "partially uncured" within the meaning of the present disclosure. It is expected that if the energy provided is less than 2 times Ej, then the surface will be in an unfinished state. Figure 8 A surface 42 is shown forming an unfinished layer for which the light dose has been set to be lower than or equal to the Jacob energy Ej.

[0107] The Jacobs energy Ej corresponds to the minimum curing surface energy for a given curable material of a given thickness to harden the entire given thickness to a solid state sufficient to be measured according to the Jacobs methodology. The Jacobs energy Ej is obtained from the Jacobs equation as shown below:

[0108] Ej=Ec*exp(th / Dp)

[0109] Wherein, "th" is the thickness of the optical element 40, "Dp" is the light depth penetration value of the curing surface energy within the curable material, and "Ec" is the critical Jacobs energy defined for the curable material.

[0110] In the case of acrylate monomers cured by a free radical chain growth polymerization process, the corresponding conversion Cv of the material considered to be solid (i.e., having received at least the Jacobs energy) is typically around 60% to 80%. Based on this conversion Cv, the conversion of the monomer is sufficient to render the polymerized material in a solid state, even if the fabricated device requires an increased conversion to have adequate mechanical properties. Accordingly, for acrylate monomers, it is contemplated that the advantages of some embodiments of the present disclosure may apply to conversions of less than 80% or 60%.

[0111] like Figure 7 As shown, the light depth penetration value Dp and the critical Jacobs energy Ec are obtained from a working curve 60 obtained from a Jacobs experiment. The experiment includes: irradiating a curable material (here, a resin) with a set of known curing surface energies; forming a plurality of samples that have been irradiated with different curing surface energies, or potentially forming a sample including different regions irradiated with different curing surface energies; and measuring the corresponding polymerized thickness of the measurable solid material for each sample or sample region. Working curve 60 is a semi-logarithmic plot of the measured thickness of the measurable solid polymerized material as a function of the natural logarithm (ln) of the curing surface energy E.

[0112] The application and spreading of the surface 42 can be carried out by the techniques commonly used in the field of ophthalmology, such as, in particular, a dipping process, a spraying process, a spin coating process, an inkjet process or a polymer jet. In order to avoid the risk of damage and inclusion of dust during transportation. The coating device can be implemented in an additive manufacturing machine (printing machine or DLP-SLA machine) or in a dedicated unit connected to the printing machine.

[0113] A control process can be implemented in the method according to the invention. A surface measuring device can be used to define suitable coating conditions. This is particularly useful when using inkjet / polymer jet technology, in which the amount of dispensed resin can be calculated depending on the (X, Y) position. The surface measuring device is preferably a non-contact measuring device.

[0114] The surface measuring device is, for example, an optical measuring device using a phase deflection measuring technique. In this case, it is preferred to use a wavelength of light that does not activate the polymerization of the resin, in particular UV light. Alternatively, the surface measuring device uses, for example, an interferometric measurement process. It is preferred to use a stitching device in conjunction with such an interferometric measurement process. These processes can measure by reflection, or by transmission and deflection of light. In reflection, for example, non-transmitting wavelengths can be used to work in order to avoid secondary reflections from another surface of the optical component, or from secondary reflections from the interface between the coating and the unfinished surface. The wavelength is preferably selected so that it does not react with photoinitiators present in the unfinished surface material.

[0115] The manufacturing method can be performed using a closed-loop process to better monitor the characteristics of the final optical element 40. Fig. 9 An example of such a control closed-loop process is shown in .

[0116] The unfinished surface 42 is printed out 100 and then measured 110 by a surface measurement device. The properties of the first coating are determined 120 depending on the measurements made on the surface 42. These properties preferably include at least the thickness of the first coating. In addition, the frequency or amplitude of the corrugations or roughness and the average amplitude of the roughness can be considered to determine the required rheological properties of the first coating: thickness, viscosity, surface tension, etc. The first coating is then deposited 130 onto the surface 42 and measured 140 by the surface measurement device.

[0117] The measurements taken on the first coating are compared 150 to the acceptance requirements (e.g., the surface quality of the optical element 40 or the thickness of the first coating). If the optical element 40 is acceptable, the control process is complete and the first coating surface is fully cured 160 in an inert (oxygen-free) atmosphere. If the optical element 40 is unacceptable, the first coating is cured 170 in an oxygen atmosphere. An additional coating is calculated 180 and then deposited 190 onto the first coating. The additional coating is also measured 140. Another comparison 150 is made to determine whether the optical element 40 is acceptable with this additional coating. Thus, a closed loop is formed to determine the nature and amount of the additional coating so that the optical element 40 is acceptable.

[0118] In the above example, the surface measurement was performed before curing. Alternatively, the surface measurement can be performed after curing in an oxygenated atmosphere.

[0119] The hardenable coating liquid 46 is a curable material. In an embodiment, the curable material of the hardenable coating liquid 46 is substantially the same as the curable material of the volume element 14. In fact, using the same material for the hardenable coating liquid 46 and the volume element 14 facilitates the spreading, bonding and merging of the hardenable coating liquid 46 on the material of the unfinished surface of the optical element. In addition, using the same material allows the refractive index of the layers to be the same. Here, "substantially" means that the hardenable coating material will include (multiple) monomers (in apparently identical proportions) of the material used to form the predetermined volume element of the optical element, while possibly having different additives, or different concentrations of additives or solvents suitable for changing the rheological properties of the hardenable coating material (such as spreading properties or leveling properties). The exception to be noted is that some additives may be in monomer form, with the mass of the monomer being less than 15%.

[0120] In an embodiment, a plurality of layers of hardenable coating liquid are spread successively over the surface of the optical element, and for all layers the curable material of the hardenable coating liquid 46 is substantially the same as the curable material of the volume element 14. Alternatively, it may be different for some layers, and typically the first layer applied in direct contact with the unfinished surface will have substantially the same material as the curable material of the volume element.

[0121] The material of the hardenable coating liquid 46 preferably comprises at least one type of initiator suitable for initiating polymerization of the polymerizable or curable material of the volume element 14 .

[0122] The coating parameters should be adjusted depending on factors such as coating technique, resin rheological behavior, height of volume element 14, concavity and curvature of the surface, area to be covered, etc.

[0123] It should be noted that in order to have a self-leveling coating, it is preferred to have as high a surface tension as possible. In order to obtain good wetting between the solid surface and the coating liquid, it is preferred to have a minimum contact angle A, below 90°. The contact angle A is related to the surface energy Ess of the solid, the surface energy Esl between the solid and the liquid, and the surface tension T of the liquid by the following equation:

[0124] Ess=T cos(A)+Esl

[0125] Therefore, A = arcos([Ess-Esl] / T)

[0126] Therefore, increasing the surface tension T increases the contact angle and decreases wettability.

[0127] Conversely, increasing Ess or decreasing Esl decreases the contact angle and increases wettability.

[0128] Thus, one desires a low surface tension for good wetting of the coating on the surface and a high surface tension for good self-leveling properties.

[0129] The inventors have found that forming the surface with an unfinished material reduces the surface energy Esl between the hardenable coating liquid and the surface and increases the surface energy Ess of the surface. Accordingly, the use of an unfinished surface enables the wetting characteristics of the surface with respect to the hardenable coating liquid to be improved. This improves the spreading of the hardenable coating liquid on the surface and facilitates the filling of any depressions or holes in the surface.

[0130] Further, reducing the surface energy Ess between the hardenable coating liquid and the surface and increasing Esl can make the hardenable coating liquid have a higher surface tension while still maintaining a low contact angle. Therefore, a material with improved self-leveling properties can be used while still being able to spread the hardenable coating material well on the surface.

[0131] Further, it should be noted that when using unfinished surfaces that are partially liquid or uncured within the meaning of the present disclosure, the wettability mechanism changes from the wettability of liquid to solid to the miscibility of liquid to liquid. The miscibility mechanism is not mainly driven by the surface tension of the coating liquid, but by the solubility parameters of the two liquids (such as polarity, dispersion, molecular weight, hydrogen bonding, van der Waals forces, etc.). Accordingly, in the case of uncured or partially liquid unfinished surfaces, the method of the present disclosure enables high wettability while having little effect on the surface tension of the hardenable coating liquid. Therefore, a hardenable coating liquid can be used whose surface tension is higher than the wettability of the liquid to the solid. This phenomenon is increased if the material of the coating liquid is chemically close to the material of the unfinished surface.

[0132] The rheological behavior of the hardenable coating liquid 46 can be modified by rheological additives for better filling and / or leveling / stretching. The following additives can be used: surface additives, air release additives (when solvents are used), tackifiers, coupling agents, wetting and dispersing additives (in the case of filled coatings), viscosity modifiers (which can sometimes be monomers), and more general rheology modifiers.

[0133] These rheological additives can be mixed into the curable material or added during deposition.

[0134] The rheological behavior and coating parameters can be adapted for each hardenable coating. For example, the filling and leveling capabilities can be increased only for the additional coating 52. This capability can then be gradually adapted for each additional layer to enhance the leveling behavior.

[0135] The coating thickness of each layer may be different. Depending on the additive manufacturing technology used, the total coating thickness is preferably at least about the height of the recess 18 (step), for example between 1 μm and 200 μm.

[0136] The hardenable coating liquid 46, applied as a single layer or multiple layers, coats the surface 42 with a smoothing layer having a coating thickness 54 greater than the depth dimension 56 of the depression 18. Figure 4 As shown, the thickness of the layer and the depth dimension 56 of the recess 18 are defined along the thickness axis Z. The depth dimension of the recess 18 refers to the length along the thickness axis Z between the upper surfaces of two consecutive layers of the volume element 18. The coating thickness 54 is preferably considered along the thickness axis Z at a point located on the hollow between two layers or volume elements 14 on the surface. Alternatively, the coating thickness 54 can be defined by the shortest distance between the hollow between two layers or volume elements of the surface 42 of the optical element 40 and the outer surface of the hardenable coating and / or the outer surface 48 of the optical element. This outer surface 48 corresponds to the outer surface 48 of the optical element 40 when it is fully cured (including the curing of the at least one hardenable coating).

[0137] Alternatively or in combination, the coating thickness 54 is greater than the average thickness dimension of the predetermined volume element 14. The average thickness can be calculated by calculating the average of the thickness of each layer and / or voxel used to make the optical element along the Z axis. Preferably, the coating thickness 54 is greater than or equal to at least 1.5 times this depth dimension 56 or the average thickness dimension.

Claims

1. A method for manufacturing an optical component having at least one optical function, the method comprising: - manufacturing at least a portion of an optical element using an additive manufacturing process by successively aggregating a plurality of predetermined volume elements of a polymerizable material, the portion of the optical element being configured to provide at least a portion of the optical function of the optical component, the additive manufacturing being performed such that the optical element comprises an unfinished surface, such that a layer having the unfinished surface has, over at least part of its thickness and at least on the unfinished surface, a conversion or polymerization rate that is lower than that desired for the finished optical element and has a non-zero conversion or polymerization rate over at least part of its thickness, the unfinished surface having a relief pattern formed by traces of the additive manufacturing process and having at least one depression relative to an average curved surface of the unfinished surface, - applying and spreading a layer of a hardenable coating liquid to the unfinished surface, the hardenable coating liquid being configured to at least partially fill the at least one recess, - Hardening the hardenable coating liquid layer.

2. The method according to claim 1, wherein: Prior to the applying and spreading steps, the unfinished surface is at least partially uncured.

3. The method according to claim 2, wherein the unfinished surface is formed by predetermined volume elements that form the optical element, and the predetermined volume elements have a non-zero polymerization rate, which is less than or equal to the light that has received 2 times with the cured surface energy representing Jacobs energy.

4. The method according to claim 2, wherein: The unfinished surface is an inhibited layer formed by end portions of a predetermined volume element forming a surface portion of the optical element, and polymerization has been inhibited in the inhibited layer during the additive manufacturing process.

5. The method according to any one of claims 1 to 4, wherein: The hardenable coating liquid is a polymerizable coating liquid.

6. The method according to claim 5, wherein: The hardenable coating liquid comprises at least one type of initiator suitable for initiating polymerization of the polymerizable material used to manufacture the optical element.

7. The method according to any one of claims 1 to 4 and 6, wherein The polymerizable material forming the predetermined volume element of the optical component and the hardenable coating liquid comprise the same monomer.

8. The method according to claim 5, wherein: The polymerizable material forming the predetermined volume element of the optical component and the hardenable coating liquid comprise the same monomer.

9. The method according to any one of claims 1 to 4 and 6, wherein: The absolute difference between the refractive index of the polymerizable material forming a predetermined volume element of the optical element in the hardened state and the refractive index of the hardenable coating liquid in the hardened state is less than 0.

02.

10. The method according to claim 5, wherein: The absolute difference between the refractive index of the polymerizable material forming a predetermined volume element of the optical element in the hardened state and the refractive index of the hardenable coating liquid in the hardened state is less than 0.

02.

11. The method according to any one of claims 1 to 4, further comprising applying and spreading at least one additional hardenable coating liquid layer onto the hardenable coating liquid layer or onto another additional hardenable coating liquid layer, and making the hardenable coating liquid layer or the another additional hardenable coating liquid layer only partially cured before applying and spreading the additional hardenable coating liquid layer.

12. The method according to claim 10 further comprises applying and spreading at least one additional hardenable coating liquid layer onto the hardenable coating liquid layer or onto another additional hardenable coating liquid layer, and causing the hardenable coating liquid layer or the another additional hardenable coating liquid layer to be only partially cured before applying and spreading the additional hardenable coating liquid layer.

13. The method according to any one of claims 1 to 4 further comprises applying and spreading at least one additional hardenable coating liquid layer onto the hardenable coating liquid layer or onto another additional hardenable coating liquid layer, and making the hardenable coating liquid layer or the another additional hardenable coating liquid layer at least partially uncured or having suppressed end portions or sublayers before applying and spreading the additional hardenable coating liquid layer so as to promote adhesion of the additional hardenable coating liquid layer thereto.

14. The method according to claim 10 further includes applying and spreading at least one additional hardenable coating liquid layer onto the hardenable coating liquid layer or onto another additional hardenable coating liquid layer, and making the hardenable coating liquid layer or the other additional hardenable coating liquid layer at least partially uncured or having suppressed end portions or sublayers before applying and spreading the additional hardenable coating liquid layer so as to promote adhesion of the additional hardenable coating liquid layer thereto.

15. The method according to claim 11, wherein: The hardenable coating liquid layer and the additional hardenable coating liquid layer provide the optical element with a smoothing layer having a total thickness greater than the depth dimension of the recesses and / or greater than the average thickness dimension of the predetermined volume elements.

16. The method according to claim 12, wherein: The hardenable coating liquid layer and the additional hardenable coating liquid layer provide the optical element with a smoothing layer having a total thickness greater than the depth dimension of the recesses and / or greater than the average thickness dimension of the predetermined volume elements.

17. The method according to any one of claims 1 to 4, wherein: Prior to the applying and spreading steps, the unfinished surface of the optical element is not completely cleaned, so that before the hardenable coating liquid layer is applied and spread on the unfinished surface, the unfinished surface comprises a layer or sub-layer of curable liquid material.

18. The method according to claim 16, wherein: Prior to the applying and spreading steps, the unfinished surface of the optical element is not completely cleaned, so that before the hardenable coating liquid layer is applied and spread on the unfinished surface, the unfinished surface comprises a layer or sub-layer of curable liquid material.

19. The method according to any one of claims 1 to 4, wherein: The applying and spreading steps are performed by at least one of a dipping process, a spraying process, a spin coating process, an inkjet process, and polymer jetting.

20. The method according to claim 18, wherein: The applying and spreading steps are performed by at least one of a dipping process, a spraying process, a spin coating process, an inkjet process, and polymer jetting.

21. The method according to any one of claims 1 to 4, wherein: The optical element includes a plurality of layers formed by the plurality of predetermined volume elements and forming a curved profile curve, and the concavo-convex pattern of the unfinished surface is a step pattern formed by edges of the layers.

22. The method according to claim 20, wherein: The optical element includes a plurality of layers formed by the plurality of predetermined volume elements and forming a curved profile curve, and the concavo-convex pattern of the unfinished surface is a step pattern formed by edges of the layers.

23. A method for manufacturing an optical element, the method comprising providing an optical element with an unfinished surface, the unfinished surface having a step pattern such that the optical element is not completely smooth, the method comprising: - applying and spreading a hardenable coating liquid on the unfinished surface of the optical element so as to cover the step pattern of the optical element, - hardening said hardenable coating liquid present on said unfinished surface, Wherein, before applying the hardenable coating liquid, the surface having the step pattern is an unfinished surface, so that the layer having the unfinished surface has a conversion rate or polymerization rate lower than the conversion rate or polymerization rate expected for the finished optical element over at least part of its thickness and at least on the unfinished surface, and has a non-zero conversion rate or polymerization rate over at least part of its thickness.

24. The method according to claim 23, wherein: Prior to the applying and spreading steps, the unfinished surface is at least partially uncured.

25. The method of claim 24, wherein the unfinished surface is formed by predetermined volume elements that form the optical element, and the predetermined volume elements have a non-zero polymerization rate that is less than or equal to light that has received 2 times having a cured surface energy representing Jacobs energy.

26. The method according to claim 25, wherein: The unfinished surface is an inhibited layer formed by end portions of a predetermined volume element forming a surface portion of the optical element, and polymerization has been inhibited in the inhibited layer during the additive manufacturing process.

27. The method according to any one of claims 25 to 26, wherein: The hardenable coating liquid is a polymerizable coating liquid.

28. The method according to claim 27, wherein: The hardenable coating liquid includes at least one type of initiator suitable for initiating polymerization of the polymerizable material used to make the optical element.

29. The method according to any one of claims 25 to 26 and 28, wherein The polymerizable material forming the predetermined volume element of the optical component and the hardenable coating liquid comprise the same monomer.

30. The method of claim 27, wherein: The polymerizable material forming the predetermined volume element of the optical component and the hardenable coating liquid comprise the same monomer.

31. The method according to any one of claims 25 to 26 and 28, wherein The absolute difference between the refractive index of the polymerizable material forming a predetermined volume element of the optical element in the hardened state and the refractive index of the hardenable coating liquid in the hardened state is less than 0.

02.

32. The method of claim 27, wherein: The absolute difference between the refractive index of the polymerizable material forming a predetermined volume element of the optical element in the hardened state and the refractive index of the hardenable coating liquid in the hardened state is less than 0.

02.

33. The method according to any one of claims 25 to 26, further comprising applying and spreading at least one additional hardenable coating liquid layer onto the hardenable coating liquid layer or onto another additional hardenable coating liquid layer, and making the hardenable coating liquid layer or the another additional hardenable coating liquid layer only partially cured before applying and spreading the additional hardenable coating liquid layer.

34. The method according to claim 32 further includes applying and spreading at least one additional hardenable coating liquid layer onto the hardenable coating liquid layer or onto another additional hardenable coating liquid layer, and causing the hardenable coating liquid layer or the another additional hardenable coating liquid layer to be only partially cured before applying and spreading the additional hardenable coating liquid layer.

35. The method according to any one of claims 25 to 26 further comprises applying and spreading at least one additional hardenable coating liquid layer onto the hardenable coating liquid layer or onto another additional hardenable coating liquid layer, and making the hardenable coating liquid layer or the another additional hardenable coating liquid layer at least partially uncured or having suppressed end portions or sublayers before applying and spreading the additional hardenable coating liquid layer so as to promote adhesion of the additional hardenable coating liquid layer thereto.

36. The method according to claim 32 further includes applying and spreading at least one additional hardenable coating liquid layer onto the hardenable coating liquid layer or another additional hardenable coating liquid layer, and making the hardenable coating liquid layer or the other additional hardenable coating liquid layer at least partially uncured or having suppressed end portions or sublayers before applying and spreading the additional hardenable coating liquid layer so as to promote the adhesion of the additional hardenable coating liquid layer thereto.

37. The method of claim 33, wherein: The hardenable coating liquid layer and the additional hardenable coating liquid layer provide the optical element with a smoothing layer having a total thickness greater than the depth dimension of the recesses and / or greater than the average thickness dimension of the predetermined volume elements.

38. The method of claim 34, wherein: The hardenable coating liquid layer and the additional hardenable coating liquid layer provide the optical element with a smoothing layer having a total thickness greater than the depth dimension of the recesses and / or greater than the average thickness dimension of the predetermined volume elements.

39. The method according to any one of claims 23 to 26, wherein: Prior to the applying and spreading steps, the unfinished surface of the optical element is not completely cleaned, so that before the hardenable coating liquid layer is applied and spread on the unfinished surface, the unfinished surface comprises a layer or sub-layer of curable liquid material.

40. The method of claim 38, wherein: Prior to the applying and spreading steps, the unfinished surface of the optical element is not completely cleaned, so that before the hardenable coating liquid layer is applied and spread on the unfinished surface, the unfinished surface comprises a layer or sub-layer of curable liquid material.

41. The method according to any one of claims 23 to 26, wherein: The applying and spreading steps are performed by at least one of a dipping process, a spraying process, a spin coating process, an inkjet process, and polymer jetting.

42. The method of claim 40, wherein: The applying and spreading steps are performed by at least one of a dipping process, a spraying process, a spin coating process, an inkjet process, and polymer jetting.

43. The method according to any one of claims 25 to 26, wherein: The optical element includes a plurality of layers formed by the plurality of predetermined volume elements and forming a curved profile curve, and the concavo-convex pattern of the unfinished surface is a step pattern formed by edges of the layers.

44. The method of claim 42, wherein: The optical element includes a plurality of layers formed by the plurality of predetermined volume elements and forming a curved profile curve, and the concavo-convex pattern of the unfinished surface is a step pattern formed by edges of the layers.

Citation Information

Patent Citations

  • Smoothing of 3D printed lenses

    WO2017062857A1

  • Smoothing of 3D printed lenses

    CN108136667A

  • Method of manufacturing spectacle lenses containing fine diamond particles

    JP2016024456A